2011
DOI: 10.3892/ijmm.2011.722
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate prevents palmitate-induced apoptosis in osteoblastic MC3T3-E1 cells through the NF-κB signaling pathway

Abstract: Abstract. Osteoporosis is a bone condition defined by low bone mass and increase of fracture risk due to imbalance between bone resorption by osteoclasts and bone formation by osteoblasts. Low bone mass is likely to be due to the alteration of the osteoclast and osteoblast lifespan through regulated apoptosis. Saturated fatty acid (SFA) intake is negatively associated with bone mineral density (BMD). Furthermore, SFA induces apoptosis in osteoblastic cell lines. Bezafibrate could increase bone mass in intact m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In this study, it was found that gossypol treatments decreased osteoblast cell viability. The inhibition of cell apoptosis by gossypol was mainly executed through activation of caspase-3 and caspase-9, two critical executors of intrinsic apoptotic caspases [21, 22]. Hence, gossypol promoted bone formation mainly through inhibiting osteoblast cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that gossypol treatments decreased osteoblast cell viability. The inhibition of cell apoptosis by gossypol was mainly executed through activation of caspase-3 and caspase-9, two critical executors of intrinsic apoptotic caspases [21, 22]. Hence, gossypol promoted bone formation mainly through inhibiting osteoblast cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies indicate that SFAs increase bone resorption by elevating the expression of inflammatory cytokines and the receptor activator of NF-κβ ligand [33]. SFA mediates osteoclastogenesis and may decrease osteoclast apoptosis [29]. Additionally, SFAs interfere with osteoblastogenesis and bone formation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a high fat diet rich in SFA also impairs lipid metabolism that may indirectly prevent osteoclast senescence and apoptosis [158160]. Moreover, SFA mediates osteoclastogenesis and bone resorption possibly by increasing cellular oxidative stress [160,161] and the activity of inflammatory cytokines (IL1β, IL-6, TNFα) [162,163], all of which would have a negative effect on bone. Combined, these cellular and observational studies indicate that high fat feeding using different fatty acids may contribute to differential effects on bone health.…”
Section: Dietary Energy and Fat On Bone In Preclinical Studiesmentioning
confidence: 99%